1993
DOI: 10.1111/1467-9566.ep11346886
|View full text |Cite
|
Sign up to set email alerts
|

Patients with terminal cancer who use alternative therapies: their beliefs and practices

Abstract: This paper examines the extent to which patients who have been diagnosed as having terminal cancer choose to use non-medical therapies. In particular it is concerned with the illness behaviour of patients who are receiving conventional cytotoxic drug and radiation treatments, who also decide to use a wide range of 'alternative' medications and therapies. The paper discusses the findings of a study of 152 patients with metastatic cancer that examined the extent to which they used alternative cancer therapies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 14 publications
5
52
2
Order By: Relevance
“…It has been argued that locus of control is not a motivational variable that shows desire or effort for control (Shapiro, 1996). In addition, the desire for control over one's own choices (Deci & Ryan, 1985), which has been found to be associated with the decision to use CM (Truant & Bottorff, 1999;Yates et al, 1993), may be different from an expectancy for control over outcomes (Burger, 1985;Burger & Cooper, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that locus of control is not a motivational variable that shows desire or effort for control (Shapiro, 1996). In addition, the desire for control over one's own choices (Deci & Ryan, 1985), which has been found to be associated with the decision to use CM (Truant & Bottorff, 1999;Yates et al, 1993), may be different from an expectancy for control over outcomes (Burger, 1985;Burger & Cooper, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…A selection of original question about CAM therapy use developed and validated by Yates et al [3] was also included in the modified questionnaire used by Boon et al We divided the questionnaire into three sections with a total of 58 questions: (1) patient and family demographics and clinical characteristics; (2) use of CAM therapies; (3) parental beliefs about conventional treatments and CAM therapies. For this study, CAM users were defined as those who reported using at least one form of CAM.…”
Section: Methodsmentioning
confidence: 99%
“…The details of this prospective cross-sectional study have been published elsewhere (Yates et al, 1993;Beadle et al, 2004) and its intent was to capture the immediate views of patients about their attitudes and beliefs following a diagnosis of advanced cancer. In summary, eligible patients had locally advanced or metastatic cancer, measurable or evaluable disease, ambulatory status (performance status ECOG 0 -3), an estimated survival between 3 months and 2 years, and a time interval since last outpatient review of less than 3 months.…”
Section: Participantsmentioning
confidence: 99%
“…Details of therapies and the practitioners who prescribed alternatives to conventional medical treatments are described elsewhere (Yates et al, 1993) in a larger sample of patients. Therapies included vitamins and tonics, methods of meditation and relaxation, special diets, faith healing, herbal remedies, and methods of detoxification and immune stimulation.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation